The role of cytoreductive surgery in multifocal/multicentric glioblastomas - Dimov, Diyan; Brainman, Daniel; Berger, Björn; Coras, Roland; Grote, Alexander; Simon, Matthias (Journal of Neuro-Oncology, 2023)
Purpose: Multifocal/multicentric glioblastomas (mGBM) account for up to 20% of all newly diagnosed glioblastomas. The present study investigates the impact of cytoreductive surgery on survival and functional outcomes in patients with mGBM. Methods: We retrospectively reviewed clinical and imaging data of 71 patients with newly diagnosed primary (IDH1 wildtype) mGBM who underwent operative treatment in 2015–2020 at the authors’ institution. Multicentric/multifocal growth was defined by the presence of ≥ 2 contrast enhancing lesions ≥ 1 cm apart from each other. Results: 36 (50.7%) patients had a resection and 35 (49.3%) a biopsy procedure. MGMT status, age, preoperative KPI and NANO scores as well as the postoperative KPI and NANO scores did not differ significantly between resected and biopsied cases. Median overall survival was 6.4 months and varied significantly with the extent of resection (complete resection of contrast enhancing tumor: 13.6, STR: 6.4, biopsy: 3.4 months; P = 0.043). 21 (58.3%) of resected vs. only 12 (34.3%) of biopsied cases had radiochemotherapy (p = 0.022). Multivariate analysis revealed chemo- and radiotherapy and also (albeit with smaller hazard ratios) extent of resection (resection vs. biopsy) and multicentric growth as independent predictors of patient survival. Involvement of eleoquent brain regions, as well as neurodeficit rates and functional outcomes did not vary significantly between the biopsy and the resection cohorts. Conclusion: Resective surgery in mGBM is associated with better survival. This benefit seems to relate prominently to an increased number of patients being able to tolerate effective adjuvant therapies after tumor resections. In addition, cytoreductive surgery may have a survival impact per se.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Biopsy; Glioblastoma; Growth patterns; Multicentric; Multifocal; Resection